PENGARUH REVITALISASI TERHADAP POLA RUANG KOTA LAMA SEMARANG - Anandya Ghifari Firdaussyah; Santy Paulla Dewi (Jurnal Riptek, 2021)
The revitalization of the Old City of Semarang has had a significant impact on the physical condition of the area. Initially, the image of the Old City of Semarang as a historical tourist destination is an ancient area with poorly maintained conditions, experiencing flooding every year, and socio-economic problems. Revitalization is one of the efforts undertaken by the government to revive the Kota Lama Semarang area which is experiencing environmental degradation or degradation. Improvement of infrastructure conditions, widening pedestrian paths, and procurement of street furniture are the main focus of the revitalization program. The purpose of this study is to analyze the effect of revitalization on changes in spatial patterns that occur in the Kota Lama Semarang area. In order to achieve these objectives, research objectives are set, namely the identification of the revitalization process, analysis of changes in spatial patterns, and analysis of the impact of revitalization on changes in regional spatial patterns in the Old City of Semarang. In this study using quantitative methods through temporal spatial analysis, descriptive analysis and comparative descriptive analysis which aims to determine the relationship between the revitalization process and changes in spatial patterns in the Kota Lama Semarang area. The results showed that revitalization affects the changes in the spatial pattern of the Kota Lama Semarang in terms of spatial use, building characteristics, accessibility, land prices and settlement characteristics. Many things have happened due to revitalization, such as the emergence of new activities in the form of commercial areas, trade areas and changes in community activities in the Kota Lama Semarang area. Spatial use control is carried out to control changes in spatial patterns that occur so that it remains in accordance with the designation of the area of the Old City of Semarang